The relationship between self-esteem and approval dependence in university students: The serial mediation of interaction anxiety and insight - ERDEN ÇINAR, SEVAL (My University, 2022)
his research examined the serial mediating effect of interaction anxiety and insight into the relationship between self-esteem and approval dependence in university students. The research group comprised 511 volunteer university students, of whom 78,7% were females and 21,3% were males. Research data was collected via “The Two-Dimensional Self-Esteem Scale”, “The Scale of Interpersonal Relationship Dimensions”, “Interaction Anxiousness Scale”, and “Insight Scale”. In analysing the data, descriptive statistics were examined and the relationship between variables was calculated using the Pearson correlation coefficient. The bootstrap method was used to test the mediation model.The mediation analysis results revealed that interaction anxiety and insight functioned as mediation variables in the relationship between self-esteem and approval dependence. According to the findings, an increase in self-esteem causes a decline in interaction anxiousness, which causes an increase in insight, which in turn leads to a decline in approval dependence. Findings related to the model that was tested were discussed following the literature. Suggestions for researchers and field practitioners were listed.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Eğitim Bilimleri; Psikolojik Danışma ve Rehberlik; Social Sciences and Humanities; Education; Educational Sciences; Guidance and Psychologicial Counseling; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Self-esteem; interpersonal relationships; approval dependence; interaction anxiety; insight; serial mediator model